Pengaruh Kepemimpinan, Komunikasi dan Pengawasan terhadap Kinerja Pegawai dengan Kedisiplinan dan Motivasi sebagai Variabel Intervening - Nugroho, Budi Eko (-)
This study aims is to determine the effect of leadership, communication and monitoring the performance of employees with discipline and motivation as an intervening variable At the Regional Development Planning Board Wonogiri. This study is a survey research. The data is primary data by sampling sample in this study was 40 employees. Sampling techniques in this study using census method used analytical tool Test Instrument Research, Testing linearity, path analysis and regression with t test, F test and R2 test. T test results showed that leadership has a significant effect on the discipline. Communications has not a significant effect on discipline. Supervision has a significant effect on discipline. Leadership has a significant effect on motivation. Communications has not a significant effect on motivation. Supervision has a significant effect on motivation. Leadership has a not a significant effect on performance. Communication has a significant effect on performance. Supervision has significant effect on performance. Employeeâ€™s discipline has not aÂ  significant effect on performance. Motivation has a significant effect on performance. The F test can be concluded simultaneously that leadership, communication, supervision, discipline and motivation have positive and significant impact on employee performance. Results The R2 total was 99.6%. This means that the employee's performance was explained by the leadership, communication, supervision, discipline and motivation of employees amounted to 99.6% and the remaining 0.4% described other variables outside the model. Leadership direct was a variable that was most effective for improving employee performance, because it has the greatest impact, positive and significant.Keywords: leadership, communication and monitoring, employee performance, discipline and motivation.